Ibrutinib monotherapy for relapse or refractory primary CNS lymphoma and primary vitreoretinal lymphoma: Final analysis of the phase II 'proof-of-concept' iLOC study by the Lymphoma study association (LYSA) and the French oculo-cerebral lymphoma (LOC) network. (August 2019) - Soussain, C.; Choquet, S.; Blonski, M.; Leclercq, D.; Houillier, C.; Rezai, K.; Bijou, F.; Houot, R.; Boyle, E.; Gressin, R.; Nicolas-Virelizier, E.; Barrie, M.; et al.
Abstract: Background: Primary central nervous system lymphomas (PCNSLs) are mainly diffuse large B-cell lymphomas (DLBCLs) of the non-germinal centre B-cell subtype, with unmet medical needs. This study aimed to evaluate the efficacy and toxicity of ibrutinib in DLBCL-PCNSL Patients and methods: This prospective, multicentre, phase II study involved patients with relapse or refractory(R/R) DLBCL-PCNSL or primary vitreoretinal lymphoma. The treatment consisted of ibrutinib (560 mg/day) until disease progression or unacceptable toxicity occurred. The primary outcome was the disease control (DC) rate after two months of treatment (P0 < 10%; P1 > 30%). Results: Fifty-two patients were recruited. Forty-four patients were evaluable for response. After 2 months of treatment, the DC was 70% in evaluable patients and 62% in the intent-to-treat analysis, including 10 complete responses (19%), 17 partial responses (33%) and 5 stable diseases (10%). With a median follow-up of 25.7 months (range, 0.7–30.5), the median progression-free and overall survivals were 4.8 months (95% confidence interval [CI]; 2.8–12.7) and 19.2 months (95% CI; 7.2-NR), respectively. Thirteen patients received ibrutinib for more than 12 months. Two patients experienced pulmonary aspergillosis with a favourable (n = 1) or fatal outcome (n = 1). Ibrutinib was detectable in the cerebrospinal fluid (CSF). The clinical response to ibrutinib seemed independent of the gene mutations in the BCR pathway. Conclusion: Ibrutinib showed clinical activity in the brain, the CSF and the intraocular compartment and was tolerated in R/R PCNSL. The addition of ibrutinib to standard methotrexate-base induction chemotherapy will be further evaluated in the first-line treatment. Clinical trial number: NCT02542514 . Highlights: Ibrutinib (560 mg/day) showed a significant clinical activity in R/R primary central nervous system lymphoma and primary vitreoretinal lymphoma. The intention-to-treat overall response rate was 52% after two 28-day cycles with activity in the brain, eyes and cerebrospinal fluid. Responses were observed even in the absence of CD79B and MYD88 mutation. The median progression-free survival was 4.8 months (95% confidence interval [CI]; 2.8–12.7). Pulmonary aspergillosis occurred in 2 patients (4%). No fatal haemorrhage occurred.